Negotiating Tradition and Modernity: The Practice of Prohibiting Marriage in the Month of Suro among Javanese Muslims in South Lampung - Supriyadi; Nik Abdul Rahim Nik Abdul Ghani (Islamic Research Publiser, 2025)
This study aims to explain the practice of prohibiting marriage in the month of Suro within Javanese customs, a tradition deeply rooted in cultural beliefs and social values. The research employs a combination of field study and library research to obtain both empirical and theoretical perspectives. Data collection techniques include interviews, observations, and documentation, allowing for a comprehensive understanding of the phenomenon. Primary data were gathered from local respondents, while secondary data were obtained from relevant literature and historical sources. To ensure data validity and authenticity, the study utilized source triangulation, and data were analyzed using the Miles and Huberman interactive model. The findings reveal that most villagers, particularly the older generation, continue to uphold the prohibition of marriage in Suro as part of their collective cultural identity. They regard this practice as a symbol of respect for ancestral traditions that must be preserved. Conversely, the younger generation demonstrates a gradual shift in perception. Many young couples view the prohibition as merely a myth without rational or religious justification, reflecting a shift in cultural values influenced by education, modernization, and changing social structures. Academically, this study contributes to enriching interdisciplinary discourse among law, culture, and religion in Indonesia. It provides a critical lens for understanding how local wisdom interacts with contemporary rationality, offering insights into the dynamic negotiation between cultural preservation and modernization. This research also serves as a reference for future studies exploring the adaptation of traditional customs within modern social realities.